Evaluating the impact of social responsibility disclosure on investment decision making by institutional investors in Singapore : a field experiment. - Koh, Hian Chye. (2008)
The primary purpose of this study is to test empirically, in a field experiment, the effects of providing general corporate social responsibility information on the decisions made by institutional investors. The second purpose is to determine respondentse perceptions of the relative importance of selected areas of social disclosures in an investment decision context.